THU0499 Anti-mullerian hormone in a cohort of young adult women with juvenile idiopathic arthritis. (15th June 2017) - Mario, C Di; Gigante, MR; Musto, A; Barini, A; Barini, A; Tolusso, B; Ferraccioli, G; Gremese, E
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) represents one of more common chronic disease of the childhood, affects young people before sixteen and persists into their reproductive years. It is reported in one study that fertility was not impaired in JIA women but potentially it can be compromised by pharmacological treatments such as the prolonged immunosuppressive therapy used in young women patients (1). The Anti-Müllerian Hormone (AMH) is secreted from granulosa ovary cells and serum levels of Anti-Müllerian Hormone are used as a measure of ovarian reserve, reflecting the number of primary follicles. Objectives: The aims of this study were to evaluate AMH serum levels in a cohort of young adult women affected from JIA, to compare these levels between patients and healthy controls and to assess whether the presence of the disease and the influence of previous exposure to disease-modifying antirheumatic drugs (DMARDs) and of other disease parameters may affect the ovarian reserve. Methods: Forty women with a diagnosis of JIA, aged 18 to 25 years and with regular menses, and 20 healthy women age-matched were evaluated. Anti-Müllerian Hormone serum levels were measured according to a 2-stage enzyme-linked immunosorbent assay (ELISA) technique using a commercially available kit (AMH Gen II ELISA; Beckman Coulter). Clinical and demographic characteristics, disease duration, previous and current therapies disease activity score on 44 joints (DAS), health assessment questionnaire (HAQ) were performed at the time of blood sample. Results: JIA patients had a mean age of 21.4±3.2 years, a disease duration of 11.5±6.6 years, a DAS of 1.22±0.58, and 12 (30%) were smokers. No significant differences were found in our cohort of JIA and healthy subjects in AMH serum levels (5.6±0.4 vs 6.6±0.6 ng/ml, respectively, p=0.5). Considering the JIA cohort, 23 patients (57.4%) were treated with methotrexate (MTX) for a mean period of 2.1±3.1 years and 20 (50%) with anti-TNF drugs for 4.3±2.3 years. Twelve JIA women (30%) were treated with both MTX and anti-TNF. No correlations were found between AMH serum levels and patients age (p=0.6), disease duration (years) (p=0.67) and duration of therapy with MTX (p=0.5) or anti-TNF (p=0.11). Dividing JIA patients according to MTX use, no differences were observed between MTX users and non users patients in AMH levels (6.0±0.5 vs 5.1±0.5 ng/ml, respectively, p=0.22), age, disease duration and other clinical characteristics. Patients expose to anti-TNF had AMH serum levels tendentially higher then non users patients (6.3±0.6 vs 4.9±0.5 ng/ml, respectively p=0.07). Conclusions: In our JIA group of young adult JIA women, ovarian reserve seems not be changed by the presence of the disease, the long disease duration and the use of immunosuppressive drugs. These findings could be important for adult JIA patients. References: Ostensen M et al. J Rheumatology 2000;27:1783–7. Disclosure of Interest: None declared